Uji Efektivitas Ekstrak Lengkuas (Alpinia Galanga) Sebagai Antibakteri Escherichia Coli - Melinda Agustin Hiala; Utma Aspatria; Rut R. Riwu (Universitas Nusa Cendana, 2019)
Food is a source of nutrition for humans and is also a source of food for microorganisms. The growth of microorganisms in foodstuffs can cause unwanted physical or chemical changes causing food to be bad for consumption. Therefore to maintain the quality, the food must be given of preservatives. However, people may misuse the preservatives leading to the low safety of food that threatens health. Natural preservatives of plants is more advisable to minimize the risk. The aim of this research was to see the effect of galangal extract (Alpinia galanga) using 60% ethyl acetate solvent in inhibiting the growth of Escherichia coli bacteria through diffusion disk method. The measured parameter was the inhibition zone formed around the disc paper with a 24-hour incubation period. This research was an experimental study by making galangal extract in certain concentrations. Based on the measurements, the average inhibitory zone diameter at three repetitions with 24 hours observation showed that the galangal extract in several concentrations effectively inhibited the growth of Escherichia coli bacteria. The result showed that the higher the concentration of the extract the larger the mean drag zone formed around the disk paper. The most effective concentration was 20 ml concentration with 25,6 mm inhibition (0.000 (P <0,05), F = 89,592).